Do narcissistic boys and girls differ in their aggression? - Oskari Lahtinen; Kätlin Peets (Taylor and Francis Inc., 2022)
Narcissistic individuals harbor self-views that are grandiose yet fragile. Evidence suggests that adult narcissists lash out when their highly inflated self-views are challenged. The present study sought to investigate whether being rejected or victimized accounts for increased aggression among adolescent narcissists. Cross-sectional self- and peer-reported data were obtained from a sample of 372 adolescents (mean age 14.4 years). Aggression measure combined self- and peer-reported aggression. Being rejected was associated with elevated aggression in narcissistic males. Being rejected or victimized was associated with having less aggression in narcissistic females. We conclude that rejection and victimization are possibly dealt with differently by narcissistic adolescent males and females.